New species of Lepidodactylus (Squamata: Gekkonidae) from New Guinea and adjacent islands - Kraus, Fred (Zootaxa, 2019)
I describe five new species of Lepidodactylus from New Guinea or adjacent islands that are members of Brown & Parker’s (1977) phenetic Groups I and II and belong to the clades identified as the L. orientalis, L. pumilus, and L. novaeguineae groups of Oliver et al. (2018a). One of the new species is restricted to an isolated mountain range on New Guinea; the remainder inhabit offshore islands ranging from 3–250 km from New Guinea. These species are distinguished from their congeners primarily by unique combinations of toe lamellar numbers and shape, numbers and distribution of enlarged precloacal/femoral scales and pores, toe webbing, toe width, and color pattern. These clades are ancient, and the ancestor of one of them has been on the East Papuan Composite Terrane for at least 28 MY, highlighting the long-term importance of that former large island in generating regional biodiversity. At least one, and probably three, of the new species are inhabitants of forest interiors; one occupies disturbed coastal areas; and the habitat of the last is currently unsurmisable. All of the new species likely have restricted geographic distributions, with four of them being limited to one or a few small islands. As a result of their small ranges, rapid habitat conversion in the ranges of some of these species, and the threat of further habitat loss in the others, most of these species are of conservation concern although it is uncertain if any of them is under immediate threat.